Thermal requirement of oilseed Brassica cultivars at different phenological stages under varying environmental conditions - Roy, Sumana; Meena, R L; Sharma, K C; Kumar, Vinod; Chattopadhyay, C; Khan, S A; Chakravarthy, N.V.K (The Indian Journal of Agricultural Sciences, 2005)
Field experiments were conducted during three post rainy (rabi) seasons of 2001-2004 at Bharatpur, New Delhi and Mohanpur to study the effect of sowing dates and cultural environment on accumulation of growing degree-days vis-a-vis occurrence of different phenological events on oilseed Brassica cultivars ’Varuna’, ’Rohini’, ’Pusa Jaikisan’ [Brassica juncea (L.) Czem. and Coss.] and ’Binoy’ (B, rapa L. var yellow sarson) sown at seven-day intervals starting from 1 October. October sown crop recorded higher seed yield due to exposure to higher growing degree-days. Variations were also noticed among locations. Equation developed from the study can be used for simulation of phenology and growth of mustard.